Implementasi Network Slicing dengan menggunakan Flowvisor untuk Mengontrol Traffic Data Packet pada Jaringan Software Defined Network - Ahmad Rizal Muttaqin; Widhi Yahya; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The rapid network growth resulted in SDN Networks will encounter heavy traffic or network traffic from various types of data packets. The density of network traffic and the different data packets will result in decreased network quality. This is due to differences in data packets that flood the network has different communication characteristics as well as the Transmission Control Protocol (TCP) packet and the User Datagram Protocol (UDP) package. The more dense and the difference of packet characteristics on network traffic, it is necessary to implement network slicing by using flowvisor to overcome the problem of decreasing SDN network performance. Through the implementation of this system obtained QOS test results throuhput TCP, throughput UDP, packet loss, and jitter. Implementation of network slicing with flowvisor has a distance average value of TCP and UDP througput better than the normal SDN network that is 380.359 and 0.535 Mbits / sec. The mean distance of packet loss and jitter value of network slicing implementation also has better value than normal SDN network that is 908,546 bytes on packet loss and 0.138 ms on jitter.